Revealed Blue: dialogues between cyanotype, creative processes and learning (Revista Apotheke, 2026)
This report presents the experience of using cyanotype as an alternative pedagogical tool in Visual Arts education, exploring its potential to enhance the creative process and expand students’ expressive possibilities. The proposal was developed within a Professional Master’s Program in Basic Education Practices, integrating art, science, and nature in a poetic and experimental way. The experience unfolded in two stages: the implementation of an educational product focused on the theme of identity, and a workshop inspired by the trajectory of botanist Anna Atkins (1799–1871), a pioneer of photography. The results show that cyanotype, by combining scientific investigation with artistic expression, stimulates students’ curiosity, sensitivity, and autonomy. The technique proved to be more than a subject to be taught—it became a way of thinking and experiencing art meaningfully, transforming light, time, and observation into language, creation, and learning.
Keywords: cyanotype; visual arts education; Anna Atkins; basic education; creative process